Analisis Karakteristik Konsumen Hotel â€œXâ€ dengan Menggunakan Metode K-Means Clustering - Hidayat, Taofik; Putro, Bramantiyo Eko (Jurnal Media Teknik dan Sistem Industri, 2020)
Abstractâ€” Hotel "X" has a problem with a marketing strategy that is incompatible with the characteristics of consumers staying at the hotel "X". This is because the hotel "X" does not yet know the characteristics of its consumers. The marketing strategy that is not optimal also affects the occupancy rate of the "X" hotel. This problem can be seen from the fluctuating number of overnight stayers. So that the number of hotel visitors is small. The purpose of this study is to determine the marketing strategy that is following the characteristics of consumers in the hotel "X", using the K-means clustering method. The research data collection was done by collecting secondary data based on historical data of Hotel "X", which amounted to 725 transactions. The data collected is data on gender, room type, travel companions, length of stay, price, area of origin, booking method. Data processing using the k-means clustering method was carried out with the help of SPSS 20. The results of the analysis of the k-means clustering method were gender, type of room booked, number of friends, length of stay, room price ordered, nationality, booking method. This study obtained 3 clusters. The first cluster is a cluster that often books economical rooms and orders online called online-low customer. The second cluster is the medium customer, namely the consumer cluster that orders middle classrooms, and the 3rd cluster which is similar to the 1st cluster but ordering through media other than online, namely the offline-manual customer.Keywordsâ€” Consumer characteristic, Hotel, K-means clustering.Â Abstrakâ€” Hotel â€œXâ€ memiliki permasalahan pada strategi pemasaran yang tidak sesuai dengan karakteristik konsumen yang menginap di hotel â€œXâ€. Hal ini dikarenakan hotel â€œXâ€ belum mengetahui karakteristik konsumennya. Strategi pemasaran yang belum maksimal juga mempengaruhi tingkat okupansi hotel â€œXâ€. Permasalahan ini terlihat dari jumlah penginap selama 1 bulan yang fluktuatif. Sehingga jumlah pengujung hotel sedikit. Tujuan penelitian ini untuk mengetahui strategi pemasaran yang sesuai dengan karakteristik konsumen di hotel â€œXâ€, dengan metode K-means clustering. Pengumpulan data penelitian dilakukan dengan cara mengumpulkan data sekunder berdasarkan data historis Hotel â€œXâ€ yang berjumlah 725 transaksi. Data yang dikumpulkan adalah data jenis kelamin, tipe kamar, teman perjalanan, lama menginap, harga, asal daerah, metode booking. Pengolahan data dengan metode k-means clustering dilakukan dengan bantuan SPSS 20. Hasil analisis dari metode k-means clustering faktor yang berpengaruh adalah jenis kelamin, tipe kamar yang dipesan, jumlah teman, lama menginap, harga kamar yang di pesan, kewarganegaraan, metode booking. Penelitian ini memperoleh 3 cluster. Cluster pertama merupakan cluster yang sering memesan kamar ekonomis dan memesan secara daring disebut Âonline-low customer. Cluster ke-2 bernama medium customer yaitu cluster konsumen yang memesan kamar kelas menengah, dan cluster ke-3 yang mirip dengan cluster ke-1 tapi memesan melalui media selain daring yaitu offline-manual customer.Kata kunciâ€” Karakteristik konsumen, Hotel, K-means clustering.Â